PENGARUH BILAH TURBIN TWISTED DAN NON-TWISTED TERHADAP STRESS DAN DISPLACEMANT PADA BILAHTURBIN ANGIN BERJENIS SAVONIUS - Farhan Muhammad Daffa (2022)
Blade is one of the important and main parts of the wind turbine , including the savonius type wind turbine which must have the best design so that it is optimal in generating power. Based on this, the authors chose the topic of stress and displacement analysis in the design of wind turbine blades. This research begins with modelling the design of the non-twist and twist 45° blades , calculating the force received by the blades until the simulation fulfils the analysis . The simulation method uses a static structure with three wind speeds. After simulating the two blade designs of the savonius type wind turbine , the wind turbine with twisted 45 ° is more optimal to choose . Although , the design has a greater maximum stress distribution value than without the twist with a stress value of 20, 79 MPa at 10 m/s wind and power 147 W but it has less deformation with deformation value of 0,26 mm and a safety factor 1,3.